The analysis of surface wave propagation in a crystal with a monoclinic structure - OPILSKA, Lidia; ŚWIDER, Janusz (Archives of Acoustics, 1982)
The present work analyzes surface wave propagation of the Rayleigh type in a monoclinic system. The problem was considered for a TGS crystal. Surface wave propagation was examined in the following planes: (010) in the , directions and in some chosen directions forming angles 20°, 40°, 60°, 130°, 150°, 170°, 180° corresponding to the direction, (100) in , directions, and (001) in and directions. The above analysis was made using an electronic computation technique. As a result of our calculations we have found that surface waves cannot propagate along and directions in the planes (001) and (100) respectively. These directions are perpendicular to the axes of symmetry and they do not lie in the (010) plane.